Ovarian Tecoma - Herrera Calmet, Abelardo (2015)
We have a short memory of tecoma ovarian functioning feminizing tumor type, addressing their histogenesis, pathology, symptoms, diagnosis, prognosis and treatment. At the same time it presented a case in which the diagnosis was made tecoma for the symptoms that the sick and especially the result of the endometrial biopsy.